2016
DOI: 10.5897/jco2016.0149
|View full text |Cite
|
Sign up to set email alerts
|

Physical characteristics and nutritional quality of salt tolerant rice genotypes

Abstract: Rice is recently introduced in Ethiopia, rice production is expanding very fast. However, the grain quality of the high yielding varieties in the country is not well characterized. The present study was carried out to evaluate some important physical characteristics and nutritional qualities of 15 rice genotypes. The experiment was conducted at Bahirdar University food and nutrition laboratory from July to August, 2015. AT 401, IR 66946 and IR 73055 had significantly the longest kernel. Most of the genotypes h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…A study on aromatic fine grain rice by Mia et al (2012) [34] indicated that the increase in grain weight occurs with increased kernel length, supporting the present study. Similarly, kernel length KL has a positive relation with kernel breadth (r = 0.653) and L/B ratio (r = 0.552), which means 1000 kernel weight of rice varieties has a strong positive association with kernel length and breadth, which means that the more refined the grain weight, slender and more elongate the grain as reported by Girma et al, 2016 [ 20] . HRR showed a non-significant, negative association with grain L/B ratio.…”
Section: Correlation Coefficients For 14 Quality Characters Among Ricementioning
confidence: 57%
“…A study on aromatic fine grain rice by Mia et al (2012) [34] indicated that the increase in grain weight occurs with increased kernel length, supporting the present study. Similarly, kernel length KL has a positive relation with kernel breadth (r = 0.653) and L/B ratio (r = 0.552), which means 1000 kernel weight of rice varieties has a strong positive association with kernel length and breadth, which means that the more refined the grain weight, slender and more elongate the grain as reported by Girma et al, 2016 [ 20] . HRR showed a non-significant, negative association with grain L/B ratio.…”
Section: Correlation Coefficients For 14 Quality Characters Among Ricementioning
confidence: 57%
“…In Ethiopia particularly in Amibara district soil salinity is the major factor for crop production [4][5][6]. Several physiological pathways have been observed to be affected by high salinity [7], at different growth stages [8,9]. Moreover, the interactions between salinity and mineral nutrition of plants are complex [10] and this negative interaction may decrease growth and consequently nutrient use efficiency [11].…”
Section: Introductionmentioning
confidence: 99%